119 Recruiting rural clinics to participate in an HPV vaccination intervention: protocol for a feasibility study and subsequent effectiveness trial. (April 2022) - Vielot, Nadja A.; Smith, Jennifer S.
Abstract : OBJECTIVES/GOALS: Rural teens have lower human papillomavirus (HPV) vaccination rates than urban teens, promoting geographical cervical cancer disparities. Giving HPV vaccination earlier than the recommended 11-12 years might increase vaccination rates. We describe a feasibility study for recruiting rural clinics to participate in early HPV vaccination studies. METHODS/STUDY POPULATION: Leveraging professional contacts, we identified two clinics in North Carolina that serve predominantly rural populations. To assess the feasibility of adapting clinic monitoring systems to promote early vaccination, we requested to review electronic medical records (EMR) to identify the size of the vaccine-eligible patient population, HPV vaccination coverage, and the accuracy of EMR queries to monitor HPV vaccination status. Next, we completed in-depth interviews with clinic staff to collect insights on perceived advantages and disadvantages of promoting early HPV vaccination at 9-10 years, and potential facilitators and barriers to doing so. RESULTS/ANTICIPATED RESULTS: We expect that existing clinic systems will easily accommodate early recommendation and administration of HPV vaccine by expanding EMR queries and vaccination status indicators to include 9- and 10-year-olds. Clinics that are interested in promoting early HPV vaccination can use these adapted tools to monitor vaccine coverage over time. From in-depth interviews we expect to encounter a mix of support and hesitation to promote early HPV vaccination, based on personal beliefs on safety and effectiveness of HPV vaccination, perceptions of adolescent HPV risk, perceptions of parental acceptability of HPV vaccination, and perceived burden of changing current clinic protocols. DISCUSSION/SIGNIFICANCE: This feasibility study's findings will help determine clinic readiness to recommend early HPV vaccination, and intervention components that maximize staff acceptability of early HPV vaccination. A subsequent randomized effectiveness study will evaluate early HPV vaccination as a method to increase rural adolescent vaccination coverage.